Accelerated tooth movement in Rsk2-deficient mice with impaired cementum formation - Cita Nottmeier; Maximilian G. Decker; Julia Luther; Simon von Kroge; Bärbel Kahl-Nieke; Michael Amling; Thorsten Schinke; Julian Petersen; Till Koehne (Nature Publishing Group, 2020)
Abstract Coffin-Lowry-Syndrome (CLS) is a X-linked mental retardation characterized by skeletal dysplasia and premature tooth loss. We and others have previously demonstrated that the ribosomal S6 kinase RSK2, mutated in CLS, is essential for bone and cementum formation; however, it remains to be established whether RSK2 plays also a role in mechanically induced bone remodeling during orthodontic tooth movement (OTM). We, therefore, performed OTM in wild-type (WT) mice and Rsk2-deficient mice using Nitinol tension springs that were fixed between the upper left molars and the incisors. The untreated contralateral molars served as internal controls. After 12 days of OTM, the jaws were removed and examined by micro-computed tomography (µCT), decalcified histology, and immunohistochemistry. Our analysis of the untreated teeth confirmed that the periodontal phenotype of Rsk2-deficient mice is characterized by alveolar bone loss and hypoplasia of root cementum. Quantification of OTM using µCT revealed that OTM was more than two-fold faster in Rsk2-deficient mice as compared to WT. We also observed that OTM caused alveolar bone loss and root resorptions in WT and Rsk2-deficient mice. However, quantification of these orthodontic side effects revealed no differences between WT and Rsk2-deficient mice. Taken together, Rsk2 loss-of-function accelerates OTM in mice without causing more side effects.